Pediatric complex regional pain syndrome following maxillofacial trauma: A case report (Indian Journal of Case Reports, 2024)
Complex regional pain syndrome (CRPS) has been described as a painful disorder with a different type of presentation and evolution months after the noxious event. The affected area shows color and vasomotor changes. Diagnosis of CRPS is hard and usually made by the Budapest criteria, as the pathological basis is still not completely known. We present this rare case that supports the idea of managing signs and symptoms with a multidisciplinary approach and supports the effective presence of a subtype of CRPS in children. This could make any other physician aware of possible diagnosis and, in the future, support the possible integration of this subtype in the Budapest criteria.